EVALUATION OF DICLOFENAC SODIUM TOXICITY AT DIFFERENT CONCENTRATIONS IN RELATION TO TIME USING BROILER CHICKEN MODEL - M. Ramzan; M. Ashraf; H. A. Hashmi; Z. Iqbal; A. A. Anjum (Journal of Animal and Plant Sciences, 2015)
Toxicity of diclofenac sodium was evaluated in relation to clinical signs, post mortem findings, liver and kidneys functions in broiler chicken model. Broiler birds (35th day) of groups A1, A2, A3 and A4 were injected diclofenac sodium at dose rate of 1.25, 2.5, 5 and 10 mg/kg body weight intramuscularly, respectively for four consecutive days. The birds of group A5 were injected with 0.2 ml/kg of physiological normal saline. Same dosage regime was followed for groups B1, B2, B3, B4 and B5 using oral route. Clinical signs observed in birds receiving 2.5, 5 and 10 mg/kg body weight diclofenac sodium were lethargy, asleep, no response to external stimuli, closed eyes, deep breathing and difficulty while standing and walking. Percent mortality recorded in different treatment groups showed increasing fashion with higher dose of diclofenac sodium used by either route. The major gross lesion was visceral gout manifested as mild to severe and widespread deposition of a mixture of white chalky material (uric acid crystals), white debris (uric acid) and varying amounts of fibrinous exudate on all the visceral organs. Serum uric acid values at 24, 48, 72 and 96 hours post-exposure were significantly higher in same groups than control and groups treated with diclofenac sodium 1.25 mg/kg body weight. Mean ± SD values of serum creatinine concentrations showed significant rise in relation to time than normal birds. A significant increase in serum AST activity was observed in samples from the birds of groups A2, A3, A4, B2, B3 and B4 at 24, 48, 72 and 96 hours after dosing (p<0.05). Values of serum ALT and ALP showed similarly rising trend with increase in the dose of diclofenac sodium used by either routes. It was concluded that diclofenac sodium is not a safe drug at higher doses by both routes.
Keywords: Diclofenac sodium; visceral gout; broiler chicken; mortality and clinical signs